Wildlife memoirs : a forester recollects - Sharma, R. C.; Dutta, J. J. (ed.); Suhas Kumar (ed.); Bhattacharya, A. K. (ed.)
This book records the personal experiences of an intrepid wildlifer. Presenting thirty-seven true wildlife stories, it shows intimate glimpses of the whole gamut of wildlife management, problems and on-the-spot solutions devised by the forest officers within the framework of law, with great devotion and application, Also, it provides deep insight into the various shades of working of a wildlifer.
Keywords: Foresters - India - Madhya Pradesh - Biography; Wildlife conservation; Wildlife management; IFoS as an author; Indian Forest Service; 1963-65 Batch